Everything augmented: on the real in augmented reality - Hanna Schraffenberger; Edwin van der Heide (Journal of Science and Technology of the Arts, 2014)
What is augmented in Augmented Reality (AR)? In this paper, we review existing opinions and show how little consensus exists on this matter. Subsequently, we approach the question from a theoretical and technology-independent perspective. We identify spatial and content-based relationships between the virtual and the real as being decisive for AR and come to the conclusion that virtual content augments that to which it relates. Subsequently, we categorize different forms of AR based on what is augmented. We distinguish between augmented environments, augmented objects, augmented humans and augmented content and consider the possibility of augmented perception. The categories are illustrated with AR (art) works and conceptual differences between them are pointed out. Moreover, we discuss what the real contributes to AR and how it can shape (future) AR experiences. A summary of our findings and suggestions for future research and practice, such as research into multimodal and crossmodal AR, conclude the paper.